High light harvesting efficiency CuInS2 quantum dots/TiO2/MoS2 photocatalysts for enhanced visible light photocatalytic H2 production. Issue 16 (6th April 2018) - Yuan, Yong-Jun; Fang, Gaoliang; Chen, Daqin; Huang, Yanwei; Yang, Ling-Xia; Cao, Da-Peng; Wang, Jingjing; Yu, Zhen-Tao; Zou, Zhi-Gang
Abstract : High light harvesting efficiency CuInS2 quantum dots/TiO2 /MoS2 composite photocatalysts were prepared for visible-light-driven photocatalytic H2 production. Abstract : Expanding the photoresponse range of TiO2 -based photocatalysts is of great interest for photocatalytic H2 production. Herein, noble-metal-free CuInS2 quantum dots were employed as a novel inorganic dye to expand the visible light absorption of TiO2 /MoS2 for solar H2 generation. The as-prepared CuInS2 /TiO2 /MoS2 photocatalysts exhibit broad absorption from the ultraviolet to near-infrared region. Under visible light irradiation ( λ > 420 nm), the CuInS2 /TiO2 /MoS2 photocatalyst with 0.6 mmol g −1 CuInS2 and 0.5 wt% MoS2 showed the highest H2 evolution rate with a value of 1034 μmol h −1 g −1 . Moreover, a considerable H2 evolution rate of 141 μmol h −1 g −1 was obtained under the irradiation of the optimized CuInS2 /TiO2 /MoS2 photocatalyst with >500 nm light. The reaction mechanism of the CuInS2 /TiO2 /MoS2 photocatalyst for photocatalytic H2 evolution was investigated in detail by photoluminescence decay study, and the results showed that the photoexcited electrons of CuInS2 can be transferred efficiently through TiO2 to MoS2 and then react with the absorbed protons to generate H2 . The reported sensitization strategy tremendously improves the visible light absorption capacity and the photocatalytic performance of TiO2 -based photocatalysts.